Chapter Os valores humanos de David-Maria Sassoli: Um ensaio - Martins, Paulo (Libere carte, 2023)
This essay is a contribution to the tribute given to David-Maria Sassoli, highlighting the human values that characterized his presidency of the European Union, namely democracy and freedom, peace, solidarity, which are the fundamental pillars for the construction of the future Europe based on the cultural diversity of each member state.